Ownership Of Flat Units For Foreigners In The Agrarian Legal Order - Hutomo, Putra; Yuhelson, H.; Ismed, Mohamad - (Faculty of Law, Universitas Pekalongan, 2024)
The aim of the research is to describe apartment units associated with investment in the property sector for ownership of apartment units for foreign citizens in Indonesia by paying attention to land rights in Indonesia, so that there is no disharmony with positive law in Indonesia. The research method uses a normative juridical legal research type. The approaches used include the statutory approach, conceptual approach, analytical approach. An analytical approach is carried out by analyzing legal material to find out what is contained in the terms used in a legal regulation conceptually, as well as understanding the regulation in practice. The results of the research are that in the UUPA there are several types of land rights, namely: (1) Ownership rights; (2) Cultivation rights; (3) Building use rights; (4) Use rights; (5) Rental rights; (6) The right to open land; (7) The right to collect forest products; (8) Other rights which are not included in the rights mentioned above will be determined by law as well as temporary rights as stated in Article 53 of the UUPA. After the enactment of Law 11/2020, the regulation of ownership of condominium units for foreigners is specifically regulated in Part Four of Land Paragraph 3 Condominium Units for Foreigners, as intended in the provisions of Articles 143 to 145. In its development to implement Constitutional Court Decision Number 91/PUU-XVIIl2020, improvements need to be made by replacing Law Number 11 of 2020 concerning Job Creation (Letter f, Considering section, Law Number 6 of 2023), as promulgated in Law Number 6 of 2023 concerning Determination of Regulations The Government Substitutes Law Number 2 of 2022 concerning Job Creation into Law (hereinafter referred to as Law 6/2023)